1985
DOI: 10.1097/00000658-198507000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Carotid Stenosis

Abstract: From 1979 to 1983, 1726 carotid endarterectomies were performed at the Cleveland Clinic. During this period, 39 men (mean age, 60 years) and 22 women (mean age, 63 years) required 65 reoperations (3.8%) for correction of recurrent carotid stenosis occurring 3 to 194 months (mean, 42 months) after previous endarterectomy at this center (N = 43) or elsewhere (N = 22). Remedial procedures were necessary because of restenosis demonstrated by routine noninvasive testing in 32 asymptomatic lesions and because of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Others have reported on outcome after redo-CEA in single center cohorts without a control group. 2430 While most of these studies reported ‘acceptable’ perioperative stroke/death rates (0 – 4.6%, all patients), several groups have reported increased risk for local complications such as nerve injury (4.6% – 21%) and wound hematoma (4.2%) 7,8,20,30,31 . We did not identify an increased risk for CNI compared to primary CEA, nor did we note an increased risk for other local complications with redo-surgery in a much larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported on outcome after redo-CEA in single center cohorts without a control group. 2430 While most of these studies reported ‘acceptable’ perioperative stroke/death rates (0 – 4.6%, all patients), several groups have reported increased risk for local complications such as nerve injury (4.6% – 21%) and wound hematoma (4.2%) 7,8,20,30,31 . We did not identify an increased risk for CNI compared to primary CEA, nor did we note an increased risk for other local complications with redo-surgery in a much larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the much higher risk of perioperative complications reported for repeat CE [34, 35, 36]it would be difficult to justify using routine surveillance to identify asymptomatic patients with disease progression to be considered for this type of intervention. furthermore, if we assume that the standard protocol for routine surveillance should be 2–3 ultrasounds in the 1st year and yearly thereafter as previously suggested by some [4, 6, 37], and that about 91,000 CE procedures [38]are performed annually, then, assuming a cost of $157 (US dollars based on medicare reimbursement [39], a conservative estimate of overall cost would be $57.1 million for the first 2 years of routine surveillance after CE in a country like the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Because others have previously reported that prior radiation therapy and redo CEA can be predictive conditions for CNI, we forced them into our prediction model. 15,16,21 However, no impact on CNI was identified among these variables: prior radiation therapy, OR 0.9, 95% CI 0.3–2.5, p = .8; and redo CEA, OR 1.0, 95% CI 0.5–2.1, p = .9.…”
Section: Resultsmentioning
confidence: 93%
“…21,25 In the current era of carotid stenting, it is likely that those with the most hostile necks are no longer selected for redo CEA. 28 …”
Section: Discussionmentioning
confidence: 99%